Changes in soluble tumor necrosis factor receptor type 1 levels and early renal function decline in patients with diabetes. Issue 6 (3rd June 2019) - MacIsaac, Richard J; Farag, Matthew; Obeyesekere, Varuni; Clarke, Michele; Boston, Ray; Ward, Glenn M; Jerums, George; Ekinci, Elif I
Abstract: The relationship between serial changes in soluble tumor necrosis factor receptor type 1 (TNFR1) levels and an early decline in estimated glomerular filtration rate (eGFR) decline remains to be defined. We found that in patients with an early decline in renal function ( n = 30), soluble TNFR1 values increased (2, 595 ± 683 vs 3, 596 ± 1, 203 pg/mL, P < 0.001) as eGFR decreased (89 ± 1 vs 51 ± 2 mL/min/1.73m 2, P < 0.001) over an 8‐year period. In contrast, there were no significant changes in soluble TNFR1 levels in patients with stable renal function ( n = 17). In a multilevel mixed effects regression model, changes in soluble TNFR1 levels were found to be independently associated with eGFR decline ( Z = −4.31, P < 0.001). An early decline in eGFR is associated with an increase in soluble TNFR levels; however, the factors driving this increase and the possible pathological role that soluble TNFR1 plays in progressive diabetic kidney disease remain to be determined. Abstract : An early decline in estimated glomerular filtration rate is associated with an increase in soluble tumor necrosis factor receptor levels; however, the factors driving this increase and the possible pathological role that soluble tumor necrosis factor receptor type 1 plays in progressive diabetic kidney disease remain to be determined.